Tourism and the city: space/place for liquid imaginaries, Puerto Vallarta (REVISTA NODO, 2010)
The following article is a preliminary result of the research conducted by the University of Guadalajara on Puerto Vallarta’s city and touristic territory. In the introduction the author examines the relationship between tourism and the city, its origins and evolution; the social, economical and cultural guidelines engendered by leisure and recreation; and its capacity to construct imaginaries and appropriations. Based on Bauman’s conception of Liquid Modernity, it analyzes the reduction of the solid world to shaping experiences and “liquid imaginaries” that form a spatially-reduced topography of touristic places and cities. Then it studies Puerto Vallarta’s development, focusing on the formal, economical, social and ecological aspects that have been modeled by national and international tourism throughout their historical evolution, and the imaginaries fashioned by leisure and recreation. The article concludes that touristic images are political representation of geographies, topographies and cultural identities that are not naïve after all, since they enclose ideological discourses conceived purposively to convert local cultural and environmental resources in touristic commodities, and to remodel identities on constant definition as well.
Keywords: Tourists’ imaginaries; leisure and consumption; social inequity